P 32 Insufficient evidence for structural gray matter alterations in late life minor depression – results from LIFE-adult study. Issue 10 (October 2017) - Polyakova, M.; Mueller, K.; Sander, C.; Lampe, L.; M. Schroeter,; Schönknecht, P.
Abstract : Background: Minor depressive episode is diagnosed when two to four depressive symptoms (including depressed mood or loss of interest) disturb the patient during at least two weeks. In late life minor depression is more prevalent than major depression. Newertheless, publications investigating pathophysiology of minor depression are missing. Methods: By means of voxel-based morphometry (VBM) we assessed structural brain magnetic resonanse images of 38 subjects with minor depressive episode and 80 healthy subjects. All participants were between 60–79 years of age and were assessed by structural psychiatric interview for DSM-IV as part of Leipzig population-based study of adults LIFE. Results: Participants did not differ with regard to age, education, body-mass index and amount of white matter lesions. However, we observed a significant sex difference between the groups. In VBM we found reduction of gray matter density in the bilateral prefrontal gyri, right superior frontal gyrus and left thalamus using a voxel threshold of p < 0.001 . However, the clusters became non-significant after correction for multiple comparisons. Discussion: In the current study we did not find sufficient evidence for alterations of gray matter density in MinD. Nevertheless, minor Depression may still be too heterogeneous although very much resembling major features of major depressive disorder. Before hypothesizing it as a functional syndrome or adjustment disorder, MinD has to be further investigated with respect to endophenotypes of major depressive disorder such as a glutamatergic deficit in the ACC in unhedonic depressed patients.